Tunnelling in the Urban Environment 2018
DOI: 10.1680/tue.63778.123
|View full text |Cite
|
Sign up to set email alerts
|

Response of full-scale piles to EPBM tunnelling in London Clay

Abstract: The installation and working test performance of four full-scale instrumented driven piles and their subsequent response to twin tunnels constructed below the pile bases are described. One pair was designed to be largely friction piles and the other pair end-bearing.Their locations relative to the new tunnels were carefully chosen to optimise the understanding of pile response at varying offsets from the centre-lines. The site conditions and the greenfield response to EPBM tunnelling at the site were described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
5
1
1
Order By: Relevance
“…It became negligible at the end of the tunnel construction, indicating little negative frictional resistance on the pile. This is clearly different from the conclusion drawn by Selemetas et al (2018), which showed a significant difference between pile top settlement and ground surface settlement at the end of shield construction in London clay strata.…”
Section: Analysis Of Monitoring Datacontrasting
confidence: 99%
See 1 more Smart Citation
“…It became negligible at the end of the tunnel construction, indicating little negative frictional resistance on the pile. This is clearly different from the conclusion drawn by Selemetas et al (2018), which showed a significant difference between pile top settlement and ground surface settlement at the end of shield construction in London clay strata.…”
Section: Analysis Of Monitoring Datacontrasting
confidence: 99%
“…Furthermore, it was investigated that the isolation pile reinforcement can strengthen the whole pile foundation, it had obviously better reinforcement effect than grout reinforcement and longeron cross bracing reinforcement (Park et al, 2015;Li et al, 2020;Lv et al, 2020;Li et al, 2021). Selemetas et al (2018) studied the effect of shield tunneling on the bearing capacity of pile foundation and the induced ground settlement in the clay strata. The results indicated that shield construction significantly reduced the bearing capacity of the pile foundation.…”
Section: Introductionmentioning
confidence: 99%
“…Research has provided empirical approaches, simplified analytical methods, and numerical analyses for the prediction of settlements and loss of capacity of existing piles due to tunnel excavation (Basile 2014;Devriendt and Williamson 2011;Jacobsz et al 2004;Hong et al 2015;Marshall 2012;Marshall and Haji 2015;Selemetas and Standing 2017;Soomro et al 2015). However, few studies have recognized the importance of pile safety factor (Dias and Bezuijen 2015;Lee and Chiang 2007;Williamson et al 2017b;Zhang et al 2011) and the role of pile installation method (displacement versus nondisplacement piles).…”
Section: Introductionmentioning
confidence: 99%
“…The interaction level is affected by the distribution of the ultimate pile capacity, which also defines the type of deep foundation: a purely-frictional pile with little base resistance, a floating pile with both shaft and base resistance, and an end-bearing pile with little shaft resistance (Mair & Williamson, 2014; Korff et al, 2016). In practice, engineers commonly use design charts that relate pile head settlement to greenfield surface settlement depending on the location of the pile base (Kaalberg et al, 2005;Selemetas, 2005;Selemetas & Standing, 2017), as shown in Figure 1. Alternatively, an empirical method can be used where pile settlement is taken as the greenfield settlement at (i) the surface, (ii) two-thirds the pile depth, and (iii) the pile base (i.e.…”
Section: Introductionmentioning
confidence: 99%